The Relationship between the Availability of Learning Facilities and the Interest of Parents in Sending Their Children to PAUD Miftahul Ilmi - Ferlin, Miranda; Ismaniar, Ismaniar (Universitas Negeri Padang, 2024)
This research is backgorund by the low of parents interest to send their children to the Miftahul Ilmi PAUD Institute. This is suspected because the lack of learning infrastructure available at Miftahul Ilmi PAUD. The purpose of this research is to describe: (1) availability of learning infrastructure, (2) parents' interests, and (3) the relation between the availability of learning infrastructure and the interest of parents to send their children to the Miftahul Ilmi PAUD Institute, Pancung Soal district. This research was quantitative correlational . The population in this research amounted of 122 persons which 55 persons of sampel. Using area random sampling technique. Techniques of data collection with questonanaire sheet statement. Data analysis techniques using percentage formulas and product momment correlation formulas. The result showed that: (1) The availability of learning infrastructure at Miftahul Ilmi PAUD is still low, (2) The interest of parents to send their children to Miftahul Ilmi PAUD is low, (3) There is a significant relationship between the availability of learning infrastructure and parents' interest. send their children to the Miftahul Ilmi PAUD Institute. Based of the result, it is suggested for Miftahul Ilmi PAUD institute to improve learning infrastructure, because it can attract parents to send their children to Miftahul Ilmi PAUD Institute.Keywords: learning infrastructure, parents interest